Study of the characteristics of the 6MV photon package from Varian IX linear medical accelerator using BEAMnrc code (Latakia University Journal -Basic Sciences Series, 2018)
The codes (EGSnrc, BEAMnrc) are used to simulate 6MV photon beam produced by Varian ix linear accelerator and different field size (20´20, 10´10, 4´4cm2). The simulation data is stored in a phase space file that contains complete details of the dates of each particle by tracking its path and interactions.Phase space files were analyzed using BEAMDP code to:-              Obtain energy spectrum, energy flow, distribution of the mean energy and the angular distribution of the photons and contaminant electrons on surface of water phantom and 100cm away from linear accelerator head.-              Study effect of field size on distribution of the energy spectrum 6MV.-              Study of change in distribution of mean energy between center and edge of the field size.-              Calculation the contribution of contaminant electrons within photonic beam at 21%.